Psychological Impact Evaluation of Early Marriage - Ardha Aulia Rovica Br Sembiring; Eka Puji Safitri; Nenda Valentin Tarigan; Salamah Salamah; Muhammad Farid Afiq (Universitas Muhammadiyah Enrekang, 2023)
Lower awareness of health knowledge, physical growth and development, women bearing children at early ages face higher risk of maternal health problems, disability and death, reinforces risking problems for their newborns as a result, early marriages are always being a very big issue in developing countries specially in primitive uncivilized districts of Asia including India, Pakistan and Bangladesh etc. Moreover it’s a controversial fact that in civilized society, evidences of getting married in early ages are greatly increased because of our religious beliefs, norms and social impacts. Due to early marriages young girls don’t have the ability to deal with responsibilities, early pregnancy and pregnancy-related mortality and morbidity, causing major physiological and psychological health issues in adolescent girls, resulting in losing relationship confidence and ability to maintain a healthy relationship. Purpose of the study was to evaluate the aspects of psychological disturbances occurring in married young girls along with depression rate and educational withdrawal, with comparison of unmarried young girls of the same age specifically there is a strong correlation between a woman’s age at marriage and the education that she receives. Uniformly across the countries, early marriage is associated with lower educational attainment. Observational study was conducted through multi logistic structured questionnaire and girls in b/w age of 13 to 35 were included. On the basis of above study it is concluded that early marriage, multiple responsibilities and early pregnancies are risk factors of depression and it is further evaluated that married girls are at higher level when compared with unmarried.